2016
DOI: 10.3329/bsmmuj.v9i4.30371
|View full text |Cite
|
Sign up to set email alerts
|

Relation between serum vitamin B<sub>12</sub> level and duration of treatment with carbamazepine in epilepsy patients

Abstract: <p class="Abstract">Vitamin B<sub>12</sub> levels in the serum of 58 epileptic patients receiving only carbamazepine for at least 6 months were measured. Same number of epilepsy patients with no history of taking antiepileptic medicine were taken as control. The mean level of vitamin B<sub>12</sub> in carbamazepine-treated epileptic patients was 265.5 pg/mL whereas it was 478.3 pg/mL in control. Increased duration of treatment of carbamazepine in epilepsy caused significantly decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…There were a few studies which have reported a decrease in level of B12 with carbamazepine but none of these have mentioned about neurological symptoms. [7][8][9] However two studies did not find a reduction in B12 levels. 10,11 Many of these studies were done to check the effect of long term antiepileptic therapy on cardiovascular risk due to elevated homocysteine levels as a result of vitamin B6, B12, folic acid deficiencies.…”
Section: Discussionmentioning
confidence: 92%
“…There were a few studies which have reported a decrease in level of B12 with carbamazepine but none of these have mentioned about neurological symptoms. [7][8][9] However two studies did not find a reduction in B12 levels. 10,11 Many of these studies were done to check the effect of long term antiepileptic therapy on cardiovascular risk due to elevated homocysteine levels as a result of vitamin B6, B12, folic acid deficiencies.…”
Section: Discussionmentioning
confidence: 92%